Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1097/00005768-199604000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of active recovery on plasma lactate and anaerobic power following repeated intensive exercise

Abstract: The purpose of this study was to investigate the effects of active recovery (AR) on plasma lactate concentration [La] and anaerobic power output as measured during repeated bouts of intense exercise (6 s) against increasing braking forces. Ten male subjects performed two randomly assigned exercise trials: one with a 5-min passive recovery (PR) after each exercise bout and one with a 5-min active recovery (AR) at a workload corresponding to 32% of maximal aerobic power. Blood samples were taken at rest, at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
1
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 25 publications
6
89
1
7
Order By: Relevance
“…According to the results, this amount of activity was sufficient for the removal of 67.38% of the lactate produced. The use of shorter amounts of active recovery may be less effective for the removal of lactate [23] or even contribute negatively to the attainment of maximum exercises [12]. Even after sixty minutes, the values of the IR in PRW (59.57%) and in PRL (66.68%) did not reach the value of ARW after thirty minutes of exercise.…”
Section: R Re Es Su Ul Lt Ts Smentioning
confidence: 99%
“…According to the results, this amount of activity was sufficient for the removal of 67.38% of the lactate produced. The use of shorter amounts of active recovery may be less effective for the removal of lactate [23] or even contribute negatively to the attainment of maximum exercises [12]. Even after sixty minutes, the values of the IR in PRW (59.57%) and in PRL (66.68%) did not reach the value of ARW after thirty minutes of exercise.…”
Section: R Re Es Su Ul Lt Ts Smentioning
confidence: 99%
“…30 It has been demonstrated that a period of active recovery, as opposed to passive recovery, enhances the rate of metabolic recovery. 1,33 Low-intensity exercise during the recovery phase after exercise may enhance the rate of lactate uptake and oxidation by muscle 4 and facilitate performance by enhancing the aerobic contribution to total energy turnover.…”
Section: Pre-experimental Proceduresmentioning
confidence: 99%
“…38 Also, it was reported that active recovery immediately after the event encourages recovery and reduces muscle lactate levels faster than complete rest. 41 In the present study, the active recovery interval was followed by either 5-minute massage or upper limb passive movement. After the intervention, the subjects rested for 5 minutes.…”
Section: Measurement Of Hand Grip Strength and Hand Grip Endurancementioning
confidence: 95%